Comparison of the Effectiveness of Paradox TimeTable Cure and Acceptance and Commitment Therapy Matrix on Family Adaptability and Mental Well-Being in Women with Marital Conflicts - Fatemeh sadat Hashemizadeh; Hamid Atashpour; Hadi Farhadi (روانشناسی و روانپزشکی شناخت)
Introduction: Marital conflict is an important factor in family instability, and women often suffer more from marital conflicts. Therefore, paying attention to the components that can help women cope with these challenges is necessary. Among these components are family adaptability and mental well-being, which play a crucial role in addressing the problems within their marital relationships. Aim: This study aimed to compare the effectiveness of the Paradox Time-Table Cure and the Acceptance and Commitment Therapy Matrix on family adaptability and mental well-being in women experiencing marital conflicts. Method: The study used a quasi-experimental design with pre-test, post-test, and follow-up stages. It included 45 women with marital conflicts, divided into two experimental groups (15 each) receiving Acceptance and Commitment Therapy or Paradox Time-Table Cure over ten sessions, and a control group (15) with no intervention. Assessments used the Olson (1985) Family Adaptability Questionnaire and Ryff (2002) Psychological Well-Being Scale, with data analyzed variance repeated measures and post hoc Bonferroni tests. Results: The findings showed that the Paradox Time-Table Cure and matrix of acceptance and commitment therapy were both effective on family adaptability compared to the control group. However, the efficacy of paradox therapy was higher (p=0.000). Also, the results for the mental well-being variable found only the acceptance and commitment matrix treatment to be effective and the Paradox Time-Table Cure had no effect on this component (p>0.05). Conclusion: The results showed that both methods of Paradox Time-Table Cure and matrix of acceptance and commitment therapy were effective in increasing family adaptability. But in the component of mental well-being, only the acceptance and commitment treatment matrix had a positive effect.